Influences of Intellectual Property and Capital to the Performance of the Corporate Image Award Winning Companies in Indonesia - Hariyati, Hariyati; Subroto, Waspodo Tjipto; Wahyudi, Sofa Nur Ihtiari; Riyanto, Yatim (International Journal of Economics and Financial Issues, 2017)
The purpose of this study was to analyze the relationship and influence of Intellectual Property as measured by Goodwill and Intellectual Capital, as measured by the Modified Value Added Intellectual coeficient (MVAIC) on the performance of the company that became the winner of the competition Corporate Image Award. Analysis of the use of intangible assets as a step to increase the value of the company and achieve good performance as the provision of competition in the future. Of all the population there are only 23 companies already meet the criteria to be sampled during 2011-2013. Data used in the study in the form of annual reports, financial statements and summary of performance that has been published on the official website of the Indonesia Stock Exchange. Analysis of the data used in the test Goodwill, MVAIC, and corporate performance adalaah multiple linear regression analysis. The results of this study indicate that there is a negative effect of the Property and Intellectual Capital Intelllectual positive effect on firm performance significantly. Keywords: Goodwill, MAIC, EPS, and Performance. JEL Classification: E6, O3